Heroic poets, poetic heroes : the ethnography of performance in an Arabic oral epic tradition - Reynolds, Dwight Fletcher, 1956- (Myth and poetics., 1995)
An astonishingly rich oral epic that chronicles the early history of a Bedouin tribe, the Sirat Bani Hilal has been performed for almost a thousand years. In this ethnography of a contemporary community of professional poet-singers, Dwight F. Reynolds reveals how the epic tradition continues to provide a context for social interaction and commentary. Reynolds's account is based on performances in the northern Egyptian village in which he studied as an apprentice to a master epic-singer. Reynolds explains in detail the narrative structure of the Sirat Bani Hilal as well as the tradition of epic singing. He sees both living epic poets and fictional epic heroes as figures engaged in an ongoing dialogue with audiences concerning such vital issues as ethnicity, religious orientation, codes of behavior, gender roles, and social hierarchies.